Clinical implications of pulmonary regurgitation in healthy individuals: detection by cross sectional pulsed Doppler echocardiography. Issue 5 (May 1988) - Takao, S; Miyatake, K; Izumi, S; Okamoto, M; Kinoshita, N; Nakagawa, H; Yamamoto, K; Sakakibara, H; Nimura, Y
Abstract : Pulsed Doppler echocardiography in healthy individuals often shows a disturbance of diastolic flow in the right ventricular outflow tract just below the pulmonary valve that suggests regurgitation. This disturbance of diastolic flow was studied in 50 healthy individuals and 40 patients with cardiopulmonary disease, some of whom had a pulmonary regurgitant murmur. Diastolic flow was disturbed in 39 of the 50 healthy individuals. In 32, cross sectional echocardiography gave a satisfactory image of the pulmonary valve. The characteristic Doppler signals usually lasted throughout diastole, were directed toward the right ventricular cavity, and gradually waned towards end diastole; they formed a spindle shaped area of abnormal signals that extended to within 10 mm of the coaptation of the pulmonary valve towards the right ventricular cavity and the pressure difference estimated from the signals by the modified Bernoulli equation seemed to be proportional to the normal retrograde transpulmonary pressure difference. In all 40 patients with cardiopulmonary disease, signals indicating pulmonary regurgitation were found whether or not a regurgitant murmur was present. When it was present, however, the spindle was longer than 20 mm and in patients with pulmonary hypertension the velocity of abnormal diastolic flow was higher than in healthy individuals. The Doppler signals registering disturbed flow in the healthy individuals resembled the signals caused by pulmonary regurgitation in the patients in terms of location, orientation, and configuration. These results show that healthy individuals usually have trivial pulmonary regurgitation. In practice the distance that the flow disturbance extends from the valve and estimated pressure difference across the valve are probably the most important variables for assessing the clinical significance of pulmonary valve regurgitation.